2022
DOI: 10.21203/rs.3.rs-1646150/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors associated with poor social support in schizophrenia patients who are on follow up in public hospital, Tigray, Ethiopia: unmatched case-control study

Abstract: Background: Schizophrenia is a syndrome, which is characterized by affecting of thinking, perception, emotions, language, sense of self, and behavior of an individual. Schizophrenic people are faced more difficulty than the rest in the community at the areas of their social interaction. This study aimed to identify factors associated with poor social support in schizophrenia patients who were on follow up in public health hospital in mekelle city. Methods: Data were collected using interviewer administered que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…In our study, both married and single individuals, regardless of gender, reported higher social support compared to divorced patients. In agreement with our findings, Andualem et al (2022) reported poor social support in divorced schizophrenia patients. Furthermore, higher income was associated with higher social support in both men and women.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, both married and single individuals, regardless of gender, reported higher social support compared to divorced patients. In agreement with our findings, Andualem et al (2022) reported poor social support in divorced schizophrenia patients. Furthermore, higher income was associated with higher social support in both men and women.…”
Section: Discussionsupporting
confidence: 93%